Leveling the playing field: can psychological coping resources reduce the influence of physical and technical skills on athletic performance? - Christensen, D. S.; Smith, R. E. (Anxiety, Stress and Coping, 2018)
Background and Objectives: The present study assessed the extent to which individual differences in psychological coping resources are related to athletic performance; whether they can attenuate the amount of performance variance accounted for by physical/technical skills; and whether coping resources remain significant predictors of performance when physical/technical skill level is statistically controlled.